Integration of Tax Justice Principles into Islamic Law for the Achievement of Sustainable Development Goals - Cahyoginarti; Amrin; Alwy Ahmed Mohamed (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study aims to examine how the principles of tax justice in Islamic Law can be integrated into modern tax policies to support the achievement of Sustainable Development Goals (SDGs). Theoretical framework: This study is based on the theory of justice in Islamic Law, which includes the concepts of distributive justice, benefit, and transparency, which in the context of Islamic history are realized through instruments such as zakat, kharaj, jizyah, and usyur. These principles are compared with modern taxation theory, which emphasizes the principles of justice, efficiency, and equity. Literature review: The literature review includes classical and contemporary fiqh literature related to fiscal obligations, tax laws and regulations in Indonesia, the Zakat Management Law, and official documents of the 2030 SDGs, which place economic justice as a main pillar of sustainable development. Methods: This study uses a qualitative approach with a juridical normative method through library research. Data were collected from Islamic legal sources, tax regulations, SDGs documents, and previous research results, then analyzed using content analysis to identify the relevance and potential for integrating the principles of Islamic tax justice with modern fiscal policies. Results: The results of the study indicate that the principle of tax justice in Islamic Law is oriented towards proportionality of burden based on taxpayers' ability, public welfare, and transparency of management. Integration of this principle with modern tax policy can strengthen the function of income redistribution, increase tax compliance, and support the achievement of SDG 1 (poverty alleviation), SDG 8 (inclusive economic growth), and SDG 10 (reduced inequality). Implication: These findings provide policy recommendations for the government to harmonize tax and zakat regulations, improve public fiscal literacy, and optimize the digitalization of tax and zakat payment systems to align with SDG targets. Novelty: This study offers a Hybrid Fiscal Model integration model that combines modern taxes and Islamic fiscal instruments proportionally and based on public welfare, thus creating a tax system that is not only based on Sharia values, but also relevant to the global development agenda.